Electrofocusing-enhanced localized surface plasmon resonance biosensors. Issue 41 (15th September 2015) - Zhang, Jinling; Wang, Yi; Wong, Ten It; Liu, Xiaohu; Zhou, Xiaodong; Liedberg, Bo
Abstract : An electrofocusing-enhanced plasmonic sensor was developed on a gold nanohole array to promote the capture of human troponin I while repelling serum albumin. Abstract : Localized surface plasmon resonance (LSPR) biosensors typically suffer from diffusion limited mass transport and nonspecific adsorption upon detection of biomolecules in real biofluids. We employ here a peptide-modified plasmonic gold nanohole (AuNH) array for real-time detection of human troponin I (cTnI). Applying a negative electric bias on the AuNH sensor chip enables us to attract and concentrate cTnI at the sensor surface, while repelling other proteins thus decreasing interferences due to nonspecific adsorption.